Modelos de Linguagem na Análise da Promoção de Jogos de Azar Online: Estudo de Caso do Jogo do Tigrinho no YouTube - Costa, Jessica; Rocha, Leonardo; Ferreira, Carlos H. G. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16067, 2025)
This undergraduate thesis analyzes the dissemination of gambling-related content on YouTube, focusing on the case of Fortune Tiger, which has been widely promoted by influencers in Brazil. The study approaches the issue as a stance detection task in NLP, using RoBERTa and Llama 3.1 models combined through consensus classification. The analysis of more than 130,000 comments revealed linguistic patterns, polarized engagement, and evidence of automation and textual repetition, particularly in favorable messages originating from new or influential accounts. The results demonstrate the potential of language models in undergraduate research, contributing to the debate on content regulation and the social impacts of digital gambling promotion.